Evaluasi Pendidikan dan Pengujian Bahasa: Strategi Meningkatkan Kualitas Pembelajaran di Era Global - Ahmad Aviv Al Mumtaz; Nur Fatimatuzzahroh; Ronaa Fitri Butsainah; Erni Zuliana; Zulhanan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This article comprehensively examines educational evaluation and language testing as strategic instruments for improving the quality of Arabic language learning in the global era. Through a systematic literature review of recent research from 2021 to 2026, this article identifies various evaluation models, testing techniques, and implementation challenges faced by language education institutions at national and international levels. The findings indicate that effective evaluation does not merely function as a tool for measuring students' abilities, but also as a feedback mechanism that promotes continuous improvement in the learning process. The integration of digital technology in language testing systems, the application of authentic assessment, and the development of educators' evaluative competencies are key factors in modernizing Arabic language education. This article also offers strategic recommendations for policy makers, institutional administrators, and educators in designing quality, inclusive, and globally responsive evaluation systems